Mapping local food self-sufficiency in the U.S. and the tradeoffs for food system diversity. (June 2022) - Bingham, Darren R.; Rushforth, Richard R.; Stevens, Bo; Ruddell, Benjamin L.
Abstract: The demand for 'local food' by U.S. consumers has grown markedly over the last several decades, accompanied by confusion over how to define local food. Is 'local' food defined by the location of the farm, food processing factory, distribution warehouse, or all three? Is 'local' food defined by geographic, political, or biophysical boundaries? Is 'local' solely farm-to-table or can it include factories? This study evaluates food commodity flow 'localness' using jurisdictional boundaries and physical distance to investigate the potential for food system transformation and the tradeoffs inherent to 'localizing' food production. We take a supply chain approach by making data-driven distinctions between farm-based flows of food and industrial, energy and nonfood (IENF) crops, and manufacturing/distribution flows of food and agriculturally-derived industrial inputs. We analyze the diversity, distance (a proxy for environmental impact), political boundaries, population, weight, and price (net selling value) of food commodity flows. The diversity of a community's food supply has an optimal range of zero to four-hundred miles. We find tradeoffs between food system diversity and local food sourcing, sustainability, and self-sufficiency. As communities look to improve food system resilience, they will need to balance food-miles and the other values associated with local food. Graphical abstract: Image 1 Highlights: Most U.S. counties do not source their food locally (<10%) within their boundary. We find that most U.S. communities have relatively resilient food supply chains. Commodity crops travel the least distance followed by table crops than manufactured. Urban counties produce manufactured food, but rural grow table and commodity crops. An inclusive local food definition must comprise manufactured foods and their network.